A feasibility study of a new instrument for detection of autism signs in preschool settings. Psychometric properties of the joint attention observation schedule preschool (JA-OBS preschool) - Linnsand, Petra; Hermansson, Jonas; Gillberg, Christopher; Nygren, Gudrun (Frontiers in Child and Adolescent Psychiatry, 2023)
Background Identifying signs of autism is essential for enabling timely diagnosis and intervention. Children from multiethnic and socioeconomic disadvantaged settings are typically diagnosed with autism later than their general peers. This feasibility study explored the psychometric properties of a new instrument, Joint Attention Observation Schedule Preschool (JA-OBS Preschool), in children with suspected autism. Methods Data were collected from a prospective longitudinal study of 46 children aged 2–4 years who lived in a multiethnic, low resource area. The children had been referred from the Child Health Centre to a multiprofessional team for a neuropsychiatric assessment. In the diagnostic process, the instrument JA-OBS Preschool for observation of a child's capability of engaging in joint attention was included. Descriptive statistics and Cronbach's alfa were used to analyze the psychometric properties, including internal consistency reliability and inter-rater consistency. Results All 46 children with suspected autism screened positive on the JA-OBS Preschool. The internal consistency reliability of the instrument was calculated at 0.8 (Cronbach's alfa). Percent agreement between two examiners in JA-OBS Preschool ranged from 77% to 100%. Conclusion JA-OBS Preschool was found to be a promising instrument for identifying signs of autism in children in this setting. However, further research is needed to determine the psychometric properties of the JA-OBS Preschool in a general child population as well as in a younger age group.